Assessment of caregiver willingness to vaccinate their children against COVID-19 in Saudi Arabia: a cross-sectional study - Mohammed Samannodi; Hassan Alwafi; Abdallah Y. Naser; Renan Alabbasi; Nouf Alsahaf; Rawan Alosaimy; Faisal Minshawi; Mohammad Almatrafi; Rami Khalifa; Rakan Ekram; Emad Salawati (Taylor & Francis Group, 2021)
Background Vaccination against COVID-19 is the key to controlling the pandemic. Parents are the decision makers in the case of children vaccination as they are responsible for them. This study aims to investigate the acceptability of COVID-19 vaccination for children among parents in Saudi Arabia. Methods This cross-sectional study used an online self-administered questionnaire. A 35-items questionnaire was distributed via social media platforms between June 6 and July 9-2021. Descriptive statistics were used to describe the participants' characteristics. Categorical variables were reported as frequencies and percentages. Predictors of vaccination acceptance were identified using binary logistic regression. Results A total of 581 parents were involved in this study. A majority of parents 63.9% reported that they will vaccinate their children if the vaccine becomes available. Around 40% of them confirmed that they want their child to be among the first to receive the COVID-19 vaccine. Nearly a quarter, 23.9%, reported that they will vaccinate their child against influenza this year. The most commonly reported reason for hesitancy was poor awareness about the vaccine's effectiveness on children. Adequate information about the COVID-19 vaccine was the most agreed cause to accept the vaccine. Having five or more children was a significant predictor for poor vaccination acceptance (OR: 0.42 (95%CI: 0.21-0.86), p < .05). Conclusion An appropriate proportion of parents are willing to vaccinate their children if the vaccine becomes available for children in Saudi Arabia. Public health awareness must be raised to gain public trust in the vaccination and the healthcare system.